Self-efficacy, Emotions and Optimisations of Preservice Special Education Teachers during Teaching Practicum - Suprihatin Suprihatin; SIN Kuen Fung Kenneth; YANG Lan (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
This study investigated the changes of self-efficacy, emotions, optimisation and the correlation between these teaching competences of preservice special education teachers to work in inclusive settings in Indonesia. This study was a survey with a combination of three questionnaires (TEIP, SF-LAEQ, OBI) used to gather information on the self-efficacy, achievement emotions and optimal best of 71 preservice special education teachers before and after teaching practicum in inclusive and or special school. Results reveal that the level of teaching efficacy, optimisation and positive emotions increased after teaching practicum. By contrast, the level of participants’ negative emotions decreased after teaching practicum. The correlation between the teaching competences after the practicum were varied. Based on the results, practical implication, limitation and future research are discussed.